1995
DOI: 10.1152/ajprenal.1995.269.6.f793
|View full text |Cite
|
Sign up to set email alerts
|

Parallel regulation of constitutive NO synthase and renin at JGA of rat kidney under various stimuli

Abstract: Four chronic experiments were performed to assess changes in the activity and gene expression of type I nitric oxide synthase (NOS) at the macula densa (MD) and of renin expression and immunoreactivity (IR) at the juxtaglomerular apparatus (JGA) of rat kidney, as follows: 1) two-kidney, one-clip Goldblatt hypertension (2K1C, for 3 and 40 days; sham operation for controls), 2) furosemide treatment (150 mg/kg-1.day-1 ip for 5 days), 3) chronic low-salt diet (0.02%) vs. high-salt diet (3%; both for 11 days), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 0 publications
5
95
0
Order By: Relevance
“…Results regarding the distal [NaCl] and the production of NO in MD in earlier studies are somewhat conflicting. In studies concerning the influence of sodium intake on NOS expression, it has been found that sodium deficiency stimulates nNOS expression, as do other conditions that are likely to result in reduced MD [NaCl] or transport, such as furosemide administration and unilateral stenosis of the renal artery (31,32). In contrast, high-salt diets and hyperfusion significantly inhibited nNOS mRNA expression (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results regarding the distal [NaCl] and the production of NO in MD in earlier studies are somewhat conflicting. In studies concerning the influence of sodium intake on NOS expression, it has been found that sodium deficiency stimulates nNOS expression, as do other conditions that are likely to result in reduced MD [NaCl] or transport, such as furosemide administration and unilateral stenosis of the renal artery (31,32). In contrast, high-salt diets and hyperfusion significantly inhibited nNOS mRNA expression (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In studies concerning the influence of sodium intake on NOS expression, it has been found that sodium deficiency stimulates nNOS expression, as do other conditions that are likely to result in reduced MD [NaCl] or transport, such as furosemide administration and unilateral stenosis of the renal artery (31,32). In contrast, high-salt diets and hyperfusion significantly inhibited nNOS mRNA expression (31,32). But in the other experiments in which the urinary excretions of nitrate and nitrite were measured, Shultz and Tolins (33) found that high salt intake generated more NO in MD cells.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the regulation of nNOS and renin by multiple stimuli, again there are many circumstances in which nNOS and renin protein expression are coordinately regulated. Bosse et al (1995) have shown parallel changes in renal nNOS and renin expression in the following models: two-kidney, one-clip Goldblatt hypertensive rats, chronic low-salt diet, chronic furosemide treatment, and inhibition of NOS with L-NAME. These parallel changes in NOS and renin suggest an involvement of NO formation in the regulation of renin or vice versa.…”
Section: Co-localization Of Renal Nnos and Renin In The Renal Vasculamentioning
confidence: 96%
“…The changes correspond to the levels of renal renin synthesis and to plasma renin levels under various conditions (24). The amount of renin mRNA and immunoreactive renin-containing arterioles are known to be largely co-localized and to vary in parallel (25). Quantification of nNOS was performed similarly, as described previously (25).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The amount of renin mRNA and immunoreactive renin-containing arterioles are known to be largely co-localized and to vary in parallel (25). Quantification of nNOS was performed similarly, as described previously (25).…”
Section: Immunohistochemistrymentioning
confidence: 99%